Macrophages programmed by apoptotic cells promote angiogenesis via prostaglandin E2 - Brecht, Kerstin; Weigert, Andreas; Hu, Jiong; Popp, Rüdiger; Fisslthaler, Beate; Korff, Thomas; Fleming, Ingrid; Geisslinger, Gerd; Brüne, Bernhard (The FASEB journal, 2011)
Macrophages contribute to tissue homeostasis in the developing as well as the adult organism. They promote tissue regeneration and remodeling after injury, which requires efficient neoangiogenesis. Signaling pathways activating an angiogenic program in macrophages are still poorly defined. We report that apoptotic cells (ACs), which originate from stressed or damaged tissues, can induce angiogenic properties in primary human macrophages. The signal originating from ACs is the lipid mediator sphingosine-1-phosphate (S1P), which activates S1P1/3 on macrophages to upregulate cyclooxygenase-2. The formation and liberation of prostaglandin E2 (PGE2) then stimulates migration of endothelial cells. This is demonstrated by using PGE2 receptor antagonists or a neutralizing PGE2 antibody in vitro, thereby attenuating endothelial cell migration using a Boyden chamber assay. In vivo, neutralization of PGE2 from proangiogenic macrophage supernatants blocked vessel formation into Matrigel plugs. In particular, apoptotic cancer cells shifted prostanoid formation in macrophages selectively toward PGE2 by up-regulating cyclooxygenase-2 and microsomal prostaglandin E synthase-1 (mPGES1), while down-regulating the PGE2-degrading enzyme 15-hydroxyprostaglandin dehydrogenase (15-PGDH) or prostaglandin-D synthase (PGDS). Angiogenic programming of macrophages by ACs, therefore, may control responses to tissue stress such as in tumors, where macrophages support cancer progression.
Im Titel ist die Zahl 2 tiefgestellt
Gesehen am 03.06.2022